Implementation of an electronic document management system based on network protocols - Mohd Juzaidin Ab Aziz, (Penerbit UKM, 2004)
Documents are central to the functioning of an organization. They are important as a means of communication in business process or known as workflow. Workflow management is used to keep track of the documents being produced by an organization. This paper discusses the development of a workflow management system based on the network applications protocols such as SMTP, POP3 and HTTP. The application does not require any purchasing of computer equipments such as documents server. It will use the existing e-mail and web server as the documents server